2021
DOI: 10.1093/ofid/ofab326
|View full text |Cite
|
Sign up to set email alerts
|

Vaccine-Associated Measles in a Hematopoietic Cell Transplant Recipient: Case Report and Comprehensive Review of the Literature

Abstract: Measles is a worldwide viral disease that can cause fatal complications in immunocompromised hosts such as hematopoietic cell transplant (HCT) recipients. The live attenuated measles, mumps, and rubella (MMR) vaccine is generally contraindicated post-HCT due to the risk for vaccine-associated measles. This, combined with decreasing vaccination rates due to vaccine hesitancy and the Coronavirus Disease 2019 pandemic, raise significant concerns for a measles resurgence that could portend devastating consequences… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…Fever (98.7%) was the most common symptom, as in our finding, while cough (39.5%) and coryza (26.3%), and conjunctivitis (18.4%) were less common. A literature review on VARI case reports between 1971 and 2021 identified that most VARI case‐patients recovered while three deaths were ported, whom all had underlying diseases (dysgammaglobulinemia, severe combined immunodeficiency, CD8 + T‐lymphocyte deficiency), 8 which highlights the need for screening for underlying diseases before immunizations with live‐attenuated vaccine such as the MMR vaccine.…”
Section: Discussionmentioning
confidence: 99%
“…Fever (98.7%) was the most common symptom, as in our finding, while cough (39.5%) and coryza (26.3%), and conjunctivitis (18.4%) were less common. A literature review on VARI case reports between 1971 and 2021 identified that most VARI case‐patients recovered while three deaths were ported, whom all had underlying diseases (dysgammaglobulinemia, severe combined immunodeficiency, CD8 + T‐lymphocyte deficiency), 8 which highlights the need for screening for underlying diseases before immunizations with live‐attenuated vaccine such as the MMR vaccine.…”
Section: Discussionmentioning
confidence: 99%
“…Severe complication of live MMR vaccine is a rare occurrence. There have been 66 published laboratory-cases of vaccine-derived measles to date internationally, with three fatalities occurring in individuals with primary immunodeficiency disorders [41]. Small studies suggest MMR vaccination is safe > 2 years post-HSCT [42][43][44][45].…”
Section: Live Vaccination Safetymentioning
confidence: 99%
“…Small studies suggest MMR vaccination is safe > 2 years post-HSCT [42][43][44][45]. There was one reported case of vaccine-derived measles in an individual two months-post graft versus host disease resolution, and three years post-HCST; they experienced a benign self-limiting rash [41]. There has been one case of vaccine-associated measles in an individual who was taking natalizumab, with full recovery [46].…”
Section: Live Vaccination Safetymentioning
confidence: 99%
“…I mmunocompromised individuals are at increased risk for acute measles virus (MeV) disease after infection with wild-type virus and can present with atypical or absent rash, prolonged viral shedding, or complications including pneumonitis and central nervous system (CNS) involvement. [1][2][3][4] Protection against disease is effectively accomplished through vaccination. However, some childhood malignancies present in children <5 years of age; thus, individuals may receive live attenuated vaccinations in close temporal proximity to a new diagnosis of an immunocompromising condition.…”
mentioning
confidence: 99%
“…Therefore, while vaccine associated disease is rare and less severe compared to wild-type disease, the risk of vaccine-related disease and secondary complications still exists. [4][5][6] There are individual reports of both self-limited and fatal vaccine-strain measles cases, primarily in immunocompromised individuals such as those with history of stem cell transplantation, solid organ transplantation or inborn errors of immunity (eg, severe combined immunodeficiency or defects in type I interferon production or signaling). [4][5][6][7] Measles inclusion body encephalitis (MIBE) following wild-type measles infection has also been reported in children and young adults, [8][9][10][11][12][13][14] but MIBE secondary to vaccine-strain MeV is an extremely rare entity with only 1 prior reported case 15 that occurred 8.5 months after vaccination in a child with an undiagnosed primary immunodeficiency with CD8 deficiency and dysgammaglobulinemia.…”
mentioning
confidence: 99%